Corporate taxes and multi-product exporters: Theory and evidence from trade dynamics - Lisandra Flach; Michael Irlacher; Florian Unger (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
This paper analyzes how exporters are affected by corporate tax reforms in destination markets. We introduce tax policy in a trade model of multi-product firms and show that producers face tougher competition in export markets with lower corporate tax rates. This competitive effect induces firms to reduce the number of exported products and to skew their export sales towards the better performing varieties. We estimate the effects of corporate taxes on trade dynamics by exploiting policy reforms in 45 destination countries of exports during the period 2005-2012. Our results provide strong support for competitive effects of corporate taxation.
Keywords: H25; F12; L11; 330; multi-product firms; corporate taxation; exporter dynamics; international trade